MARKETING PRICING STRATEGIES USED BY THE BRANCHES OF CHAIN STORES - Štefko, Róbert; Gburová, Jaroslava; Jurková, Jana (Journal of Advanced Studies in Finance; Vol 2 No 2 (2011): JASF Volume II Issue 2(4) Winter 2011, 2011)
The paper deals with pricing strategies in marketing of the branches of chain stores situated in Presov region (specifically in Presov region). The aims of research are to identification the most commonly used pricing strategies in marketing from the point of view of marketing managers of the branches of chain stores and the various connections between marketing pricing strategies. It includes identification of various connections between the selection of marketing pricing strategies and price adjustment strategies and global financial crises. The most commonly used pricing strategies in Presov region are strategy of main competition pricing strategy, promotional pricing strategy and discount pricing strategy. The most used strategy in price adjustments strategies is revisiting price strategy. These strategies were identified by marketing managers of branches of chain stores. One of the research aspects of selection marketing pricing strategies in branches of chain stores was global financial crisis. The global finance crisis does not have influence to selection and implementation of pricing strategy, which is used by branches of chain stores marketing management of in area of Presov region.